Tingkat Kesiapan Implementasi IFRS S1 dan S2: Studi Kasus pada Perusahaan dalam Indeks ESG Quality 45 IDX KEHATI - Nurrizkiana, Rika; Widyaningsih, Aristanti; Faisal, Muhammad (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2025)
This study aims to evaluate the level of readiness for the implementation of IFRS S1 and IFRS S2 standards through an analysis of disclosure gaps in the 2024 sustainability reports of companies listed in the ESG Quality 45 IDX KEHATI index. IFRS S1 and IFRS S2 are published by the International Sustainability Standards Board (ISSB) and are effective from January 1, 2024. The study uses a qualitative approach through content analysis using 29 main indicators of IFRS S1 and IFRS S2 which are grouped into four pillars: Governance, Strategy, Risk Management, and Metrics and Targets. The results of the study show that companies in the ESG Quality 45 IDX KEHATI index have shown fairly good initial readiness in disclosing strategic aspects and sustainability governance, but are not yet fully ready to meet all technical aspects required by IFRS S1 and S2. These findings have implications for regulators in designing transition policies and assistance for standard implementation more effectively. In addition, it is a reference for companies in building a strong internal reporting system and improving the quality of sustainability reporting.